2008
DOI: 10.1001/archotol.134.7.720
|View full text |Cite
|
Sign up to set email alerts
|

Blood Vessels of Vocal Folds

Abstract: Objective: To analyze and compare the incidence and visual characteristics of blood vessels on the superior surface of vocal folds with polyps, nodules, and minimal structural alterations (ie, sulci, cysts, and mucosal bridges).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 13 publications
0
1
0
4
Order By: Relevance
“…25 De Biase et al have reported that minimal structural alterations of the VF, including vocal sulci, are associated with higher incidence of visible vessels and vessel features such as tangles or abrupt changes in vessel caliber. 26 This may contribute to the higher standard deviation in the lesion than in the surrounding normal segments. Although sulci have typically subtle alterations in normal structure, the vessel characteristics of sulci may be enhanced by NBI, thus facilitating visualization of VF irregularities.…”
Section: Discussionmentioning
confidence: 99%
“…25 De Biase et al have reported that minimal structural alterations of the VF, including vocal sulci, are associated with higher incidence of visible vessels and vessel features such as tangles or abrupt changes in vessel caliber. 26 This may contribute to the higher standard deviation in the lesion than in the surrounding normal segments. Although sulci have typically subtle alterations in normal structure, the vessel characteristics of sulci may be enhanced by NBI, thus facilitating visualization of VF irregularities.…”
Section: Discussionmentioning
confidence: 99%
“…El 93,3 % de la muestra estudiada tuvo una mayor vascularización en la cubierta cordal al finalizar la tarea de sobrecarga. Esto se debe principalmente a la respuesta inflamatoria que provoca el constante estrés mecánico al que es sometido esta estructura (De Biase & Pontes, 2008). Esta respuesta es normal y natural, y permite que los tejidos expuestos al daño puedan recuperarse (Ahmed, 2011).…”
Section: Discussionunclassified
“…El daño que se instala en los pliegues vocales gracias a la sobrecarga se inicia con la respuesta inflamatoria (Bonilha, White, Kuckhahn, Gerlach, & Deliyski, 2012). En algunos sujetos se ha observado que esto se expresa con mayor dilatación capilar, aumento del riego sanguíneo (De Biase & Pontes, 2008), eritema (Samuel, Mahalingam, Balasubramaniyam, Boominathan, & Arunachalam, 2011) e incremento en el espesor de la mucosidad existente en el borde libre cordal (Bonilha et al, 2012).…”
Section: Tipo De Dosis Definiciónunclassified
“…nes subyacentes (6). Estas lesiones se producen debido a la dilatación o ruptura de los vasos sanguíneos a lo largo de la cubierta mucosa de la cuerda vocal, y se caracterizan por una amplia variedad de síntomas y signos, desde fatiga vocal, disfonía, diplofonía, hasta cierre glótico incompleto (4,6). Dentro de la fisiopatología se describe al trauma vocal agudo como gritar, llorar, tos excesiva, o puede estar asociado con el abuso crónico de la voz, el cual es visto principalmente en profesionales de la voz (6,7).…”
Section: Introductionunclassified
“…Las lesiones microvasculares pueden ser Durante los últimos años ha habido una variabilidad en la terminología, el concepto anomalías menores de los pliegues vocales fue acuñado por Arnold en 1958 para describir las lesiones laríngeas poco fáciles de diagnosticar, pero que producen disfonía persistente (2). Luego, en 1995, Pontes y colaboradores acuñaron el término lesiones estructurales mínimas para definir las variaciones o anormalidades discretas de la anatomía laríngea con un impacto clínico importante (3,4,5). Las lesiones vasculares de las cuerdas vocales son alteraciones en las cuales la distribución vascular habitual de los pliegues vocales se ve alterada.…”
Section: Introductionunclassified